2001
DOI: 10.1080/01652176.2001.9695091
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology: Prevalence of intestinal parasites in dogs in some urban and rural areas of Hungary

Abstract: SUMMARYA total of 490 canine faecal specimens collected in the eastern and northern regions of Hungary were examined for helminth eggs. From the results it appears that more than 50% of the dogs were infected with at least one parasite species. The prevalence of eggs (%) in the two regions was as follows: Toxocara canis (24.3-30

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
43
1
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 6 publications
15
43
1
5
Order By: Relevance
“…In the present study, the overall prevalence of helminthic parasites in examined stools of the dogs was 57 % that is in close alignment with a work which has been done on owned dogs in northern and eastern region of Hungary that total infection rate was reported 57.8 % (Fok et al 2001). Besides, a similar survey in Southern Greater Buenos Aires on coprological examination revealed 52.4 % of examined dogs excreted helminthic eggs whereas (Ramírez-Barrios et al 2004) and Katagiri and Oliveira-Sequeira (2008) reported 74, 35.5 and 34.4 %, respectively (Katagiri and Oliveira-Sequeira 2008;Makene et al 1996;Ramírez-Barrios et al 2004).…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, the overall prevalence of helminthic parasites in examined stools of the dogs was 57 % that is in close alignment with a work which has been done on owned dogs in northern and eastern region of Hungary that total infection rate was reported 57.8 % (Fok et al 2001). Besides, a similar survey in Southern Greater Buenos Aires on coprological examination revealed 52.4 % of examined dogs excreted helminthic eggs whereas (Ramírez-Barrios et al 2004) and Katagiri and Oliveira-Sequeira (2008) reported 74, 35.5 and 34.4 %, respectively (Katagiri and Oliveira-Sequeira 2008;Makene et al 1996;Ramírez-Barrios et al 2004).…”
Section: Discussionsupporting
confidence: 64%
“…For example, dog owners in remote Australian Indigenous communities have little access to commercial food. In some central European countries such as Slovakia, scraps are the main source of food for dogs [48][49][50][51]. Furthermore, the processes of domestic food purchase, preparation and housework (which would include clearing away dirty dishes and scraps) is traditionally considered "women's work".…”
Section: Discussionmentioning
confidence: 99%
“…Trichuris vulpis is one of the common intestinal helminiths in dogs in Europe 1,5,6,21 . The prevalence of 7.9% from this study fell within the wide range of values that have been reported by the above authors.…”
Section: Discussionmentioning
confidence: 99%